2014
DOI: 10.1063/1.4870975
|View full text |Cite
|
Sign up to set email alerts
|

Strain-mediated voltage control of magnetism in multiferroic Ni77Fe23/Pb(Mg1/3Nb2/3)0.7Ti0.3O3 heterostructure

Abstract: Using voltage-modified anisotropic magnetoresistance (AMR) measurement, we demonstrated a strain-mediated voltage control of magnetism in multiferroic Ni77Fe23(NiFe, 10 nm)/Pb (Mg1/3Nb2/3)0.7Ti0.3O3(PMN-PT, bulk crystal) heterostructure, even assuming a very small magnetostriction (∼0.3 ppm) for the NiFe film which has a composition close to bulk permalloy (Ni80Fe20). Influence of the magnitude of the rotating magnetic field used for AMR tests is studied. Combined AMR and theoretical analysis indicate the volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…For all the cases, the maximum AMR values are similar, varying between 2.31% and 2.62%, and being just slightly smaller than $3% observed for a Ni 77 Fe 23 /PMN-PT heterostructure. 17 The effect of the electric field pulse application is mainly reflected in the modification of the anisotropy field H a (marked in Fig. 3(b) by dashed lines) when the magnetization is aligned with the applied magnetic field.…”
Section: -2mentioning
confidence: 99%
See 2 more Smart Citations
“…For all the cases, the maximum AMR values are similar, varying between 2.31% and 2.62%, and being just slightly smaller than $3% observed for a Ni 77 Fe 23 /PMN-PT heterostructure. 17 The effect of the electric field pulse application is mainly reflected in the modification of the anisotropy field H a (marked in Fig. 3(b) by dashed lines) when the magnetization is aligned with the applied magnetic field.…”
Section: -2mentioning
confidence: 99%
“…13,14 Permalloy exhibits, however, a small magnetoelastic coupling constant, while its study on PMN-PT was made available only at finite magnetic fields. 17 Moreover, to be useful for a device, one needs a change of the resistance at zero applied voltage, which has not been demonstrated using the application-relevant electrical readout. Furthermore, for 3d-metals, Ni exhibits the highest magnetoelastic coupling and is thus the material of choice where, by determining the full field dependence of the magnetotransport properties, one can gauge the applicability of this approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The electric-field-controlled reversible magnetization rotation, which is important for practical applications in a wide range of low-power magnetic and spintronic devices [1,12], has been reported in Ni/0.7Pb(Mg 1/3 Nb 2/3 )O 3 -0.3PbTiO 3 [8,10,23] (Ni/PMN-PT) and CoFeB/PMN-PT [24] as well as the phase field simulations [8,12]. These magnetization rotations should naturally affect the electronic transport behaviors in the magnetic films [25][26][27][28]. Because the magnetization orientation in 3d-alloy films gives rise to the in-plane anisotropic resistivity owing to the spin-orbit interaction [29], the magnetization rotations can induce the variations of anisotropic magnetoresistivity (AMR) in magnetic films such as Fe 4 N [25,27], NiFe [26,28],…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that the strain mediated magneto-electric coupling 36,37 significantly alters the effective magneto-crystalline anisotropy field of magnetic grains when they are coupled to a piezo-electric active material.…”
Section: à5mentioning
confidence: 99%